Internal and external equity in compensation systems, organizational absenteeism and the role of explained inequalities. (March 2015) - Torre, Edoardo Della; Pelagatti, Matteo; Solari, Luca
We investigate how the design of compensation systems influences workers' behaviours at the organizational level by building upon the consequences of equity theory at the individual level. We identify four main gaps to fill in the existing equity-in-compensation research: i) the simultaneous analysis of internal and external inequity; ii) the distinction between inequitable and unequal compensation systems; iii) the organizational-level (rather than individual) effects of inequitable systems; and iv) the inclusion of absenteeism among the negative organizational outcomes of inequitable systems. The analysis of a sample of about 1500 Italian manufacturing firms shows that both internal and external equity are relevant factors in explaining the level of absenteeism. On the one hand, external pay equity is associated with a lower level of absenteeism, and the relationship becomes stronger when high pay levels are explained by past employees' performances. On the other hand, internal pay equity showed a more complex relationship, where blue-collar employees seem to react more in terms of absence to internal inequity than white-collars; moreover, performance-based pay policies (i.e. explained inequalities) further enhance the extent blue-collar employees react to internal pay equity. These results have important theoretical and practical implications, and confirm that the organizational consequences of workers' behaviours are not a mere reflection of individual-level decisions.